Answer:
Explanation:
We have been given a system of linear equations:
![2x+4y=20...(1)](https://img.qammunity.org/2019/formulas/mathematics/college/wlh1zdz5j0fy0wdfakuk7t9zrrzs4jw0au.png)
![3x+2y=26...(2)](https://img.qammunity.org/2019/formulas/mathematics/college/eczibyh2nf7vojm8dk6rolc4atedbyaaeg.png)
We will use substitution method to solve linear equation. From equation (1) we will get,
![x=(20-4y)/(2)](https://img.qammunity.org/2019/formulas/mathematics/college/dudms5xkj90jmbwgapk6za4ya98q0poceh.png)
Substituting this value in equation (2) we will get,
![3*(20-4y)/(2)+2y=26](https://img.qammunity.org/2019/formulas/mathematics/college/wry0b067loxw4gyf1v04l1gr30kwtv2ctq.png)
![(60-12y)/(2)+2y=26](https://img.qammunity.org/2019/formulas/mathematics/college/4spw89te751oag7q0xubzz5aouvz345kvj.png)
Let us have a common denominator.
![(60-12y)/(2)+(2*2y)/(2)=26](https://img.qammunity.org/2019/formulas/mathematics/college/v03aoe173a79fdlmvp556uzj8i1c1zczhm.png)
![(60-12y)/(2)+(4y)/(2)=26](https://img.qammunity.org/2019/formulas/mathematics/college/ekkh7e6abya5dqicfto6x1l78gsi575n6l.png)
![(60-12y+4y)/(2)=26](https://img.qammunity.org/2019/formulas/mathematics/college/irb5fq5pe39bjzp1smzi8spow9ep0ki89h.png)
![(60-8y)/(2)=26](https://img.qammunity.org/2019/formulas/mathematics/college/6tkksbhyd2mp318vm7mzc2z1tt8xym15hz.png)
![(60-8y)/(2)*2=26*2](https://img.qammunity.org/2019/formulas/mathematics/college/jqbih8e506tddqbesgpeqgk98v7ctdz0r3.png)
![60-8y=52](https://img.qammunity.org/2019/formulas/mathematics/college/evh2keyck308kj3r7g2tccfv9803ea2eko.png)
![60-60-8y=52-60](https://img.qammunity.org/2019/formulas/mathematics/college/naj8zt9bljw47hvrx1c3uxbekbkvjj38cj.png)
![-8y=-8](https://img.qammunity.org/2019/formulas/mathematics/college/jlkgwqn7vk95pnkrbvegzfne0tt7xf12b2.png)
Upon dividing both sides by
we will get,
![(-8y)/(-8)=(-8)/(-8)](https://img.qammunity.org/2019/formulas/mathematics/college/a2d3vzov6sd3mr1ximr8fm1po9zgn082lr.png)
![y=1](https://img.qammunity.org/2019/formulas/mathematics/high-school/7wxb3anhuavcqtqujp0bjfapj1jhy5fiuk.png)
Upon substituting
in equation (1) we will get,
![2x+4*1=20](https://img.qammunity.org/2019/formulas/mathematics/college/m9qh7a3vc22hxfa4gg0vy0g57a9ugul2y0.png)
![2x+4=20](https://img.qammunity.org/2019/formulas/mathematics/college/ztgpweov4dwtlbdxs6jf4wk6he6o853f6e.png)
![2x+4-4=20-4](https://img.qammunity.org/2019/formulas/mathematics/college/i30rguvsqqfy1pbhfg5sa7gm6k0d8u60mn.png)
![2x=16](https://img.qammunity.org/2019/formulas/mathematics/college/w5p3yvf3oi371h79byldp3irg1zls80fa7.png)
Upon dividing both sides of the equation by 2 we will get,
![(2x)/(2)=(16)/(2)](https://img.qammunity.org/2019/formulas/mathematics/college/d2c2nwainmrnlc45l91lxqifhpmuy5980o.png)
![x=8](https://img.qammunity.org/2019/formulas/mathematics/high-school/pp7uhztp3wdfjk86fiqme8246evlug6s3c.png)
Therefore, the solution of our given system of equations is
.